2018
DOI: 10.1007/s00432-018-2679-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between TNF-α −1031T/C gene polymorphism, plasma level of TNF-α, and risk of cachexia in head and neck cancer patients

Abstract: BackgroundMalnutrition and cachexia are frequent among head and neck cancer (HNC) patients and these syndromes are associated with both poor quality of life and unfavorable disease prognosis. Unfortunately, there are still no established biomarkers that could predict the development of cachexia. Among potential molecular alterations related to cancer cachexia, there are single-nucleotide polymorphisms (SNPs) within genes encoding pro-inflammatory cytokines such as TNF-α.The aim of the studyTo investigate TNF-α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 24 publications
0
31
0
1
Order By: Relevance
“…As the molecular mechanisms underlying cachexia have not been fully elucidated yet, new molecular biomarkers of cancer cachexia are urgently explored. In the literature, single nucleotide polymorphism in different genes and cytokines, differentially expressed alternatively spliced genes (DASGs), some cytokine (IL-6, and TNF-α) serum levels and epigenetic mechanisms have been associated with cachexia in patients with gastric, head and neck, pancreatic and lung cancer (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Additionally, recent studies have indicated that high systemic IL-6 levels are linked to worse prognosis in different cancer patients (gastric, non-small lung, pancreas etc.)…”
Section: Discussionmentioning
confidence: 99%
“…As the molecular mechanisms underlying cachexia have not been fully elucidated yet, new molecular biomarkers of cancer cachexia are urgently explored. In the literature, single nucleotide polymorphism in different genes and cytokines, differentially expressed alternatively spliced genes (DASGs), some cytokine (IL-6, and TNF-α) serum levels and epigenetic mechanisms have been associated with cachexia in patients with gastric, head and neck, pancreatic and lung cancer (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Additionally, recent studies have indicated that high systemic IL-6 levels are linked to worse prognosis in different cancer patients (gastric, non-small lung, pancreas etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Downstream cytokines regulated by MK2 include IL-1, IL-6 and TNF-α and high levels of these cytokines have been linked with worse patient outcome [17,18]. High cytokine levels contribute significantly to cancer proliferation, treatment resistance and metastasis [19,21,44].…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophilia and increased neutrophil-to-lymphocyte ratios (NLR) are markers of inflammation and are shown to be associated with decreased overall survival in HNSCC [14][15][16]. Furthermore, high expression of downstream inflammatory cytokines is associated with worse overall survival in HNSCC [17,18]. High serum IL-6 levels were associated with cancer recurrence and lower overall survival [17,19], and high plasma TNF-α levels were associated with high rates of cachexia and decreased survival in HNSCC patients [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other way round, there are studies showing that cachexia is associated with reduced expression of anti-inflammatory cytokines such as IL-10 (28). Finally, the association between cachexia and polymorphisms on genes coding for IL-8, IL-10, and TNFa has been reported in cancer patients (15,34,103).…”
Section: Inflammation and Oxidative Stress Cross Talk In The Muscle Amentioning
confidence: 99%